Awareness of dangers of using e-cigarettes among society - Zawiślak, Magdalena Kamila; Zaniuk, Marcin; Karakuła, Kaja Hanna; Krysa, Tomasz; Zimnicki, Patryk (Journal of Education, Health and Sport, 2020)
E-cigarettes were introduced as a new way of quitting smoking and became a popular alternative to regular cigarettes. For a long time, e-cigarettes were considered harmless, however year after a year, new facts about their adverse effects are being discovered. This year in the USA, using e-cigarettes caused a lot of deaths among their users because of the newly discovered disease called EVALI. According to this, we decided to make a research on awareness of dangers associated with using e-cigarettes. We prepared a survey with 283 responses and analyzed literature related to the topic. Responses showed that 71,4% used to smoke cigarettes. Moreover, 81,6% uses or has used e-cigarettes in the past, however, only 4,9% consider them harmless. The most common reasons for using e-cigarettes are: variety of liquid flavors (58,4%), desire to try something new (52,8%) and stress relief (32,9%). Quitting smoking was motivation only for 24,2% of responders. The fact that 72,3% do not plan to quit vaping is an alarming sign. Analysis of literature confirmed results of our survey, showing that there is a group of people using e-cigarettes although they have never smoked. Mostly they are under 20 years old. Results of our study imply the necessity of taking up actions aimed to increase society awareness of dangers associated with using e-cigarettes and to do more research on vaping side effects.